THE EFFECT OF FINANCIAL LEVERAGE, COMPANY VALUE, ASSET GROWTH, AND AUDITOR'S REPUTATION ON INCOME SMOOTHING PRACTICES - Yeremia Lieyono; Achmad Hizazi; Muhammad Ridwan (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study employs a collection of 48 data points derived from financial reports of healthcare companies listed on the Indonesia Stock Exchange during the period from 2020 to 2023The selection of participants was done using purposive sampling techniques, and the data were analyzed using logistic regression. The findings indicate that, simultaneously, financial leverage, company value, asset growth, and auditor have profit equalization. Partially results show that auditor reputation significantly influence income smoothing reputation practices. In contrast, company value and asset growth do suggest that capital structure and the credibility of external auditors play a more prominent explaining behavior compared to firm value and growth factors. Keywords: Income Smoothing; Financial Leverage; Company Value; Asset Growth; Auditor Reputation